TRADISI TUJUH BULANAN WANITA HAMIL DI INDONESIA (KAJIAN ANALISIS KEBUDAYAAN PERSPEKTIF AGAMA) - Annisa Aulia Rachma; Annisa Silvyani Zakia; Divia Avivah; Hasna Ainnur Azizah; Hisny Fajrussalam (Labor Program Studi Pendidikan Sosiologi, 2023)
The purpose of this research is to find out the tradition of seven monthly pregnant women in Indonesia from the perspective of Nahdhatul Ulama and Muhammadiyah religious figures. This research method uses the literature study method where the researcher collects several journals as reference material which is then processed again for discussion in the research journal. The results of this study indicate that the seven monthly tradition or what is called tingkeban is one of the traditions/ceremonies of the community that has been passed down from generation to generation from previous ancestors which developed by word of mouth from the Javanese tribe. This tradition is carried out by pregnant women when entering the 7th month of pregnancy. Generally the event is done during the day or evening. There are procedures for carrying out this tingkeban tradition, namely; 1) Sungkeman, 2) Siraman, 3) Putting free-range chicken eggs, 4) Change cloth 7 times, 5) Breaking the janur kuning wrap, 6) Splitting the ivory coconut, 7) Salvation, and 8) Dish. From the perspective of Nahdhatul Ulama and Muhammadiyah religious leaders, there are differences of opinion in carrying out this seven-month tradition. According to Nahdhatul Ulama figures it is not prohibited to carry out and not obligatory either so if you want to carry it out it is permissible, whereas according to Muhammadiyah figures carrying out this seven monthly tradition is strictly prohibited and punished heresy